Dietary Supplementation of Bacillus sp. PM8313 with β-glucan Modulates the Intestinal Microbiota of Red Sea Bream (Pagrus major) to Increase Growth, Immunity, and Disease Resistance - Jang, Won Je; Jeon, Mi-Hyeon; Lee, Su-Jeong; Park, So Young; Lee, Young-Sun; Noh, Da-In; Hur, Sang Woo; Lee, Seunghan; Lee, Bong-Joo; Lee, Jong Min; Kim, Kang-Woong; Lee, Eun-Woo; et al. (Frontiers in Immunology, 2022)
A 56-day feeding trial was conducted to determine the effect of dietary supplementation with Bacillus sp. isolated from the intestines of red sea bream on the growth performance, immunity, and gut microbiome composition of red sea bream. Three diets (a control diet and two treatments) were formulated without Bacillus sp. PM8313 or β-glucan (control, CD), 1 × 108 CFU g−1 PM8313 (BSD), and 1 × 108 CFU g−1 PM8313 + 0.1% β-glucan (BGSD). At the end of the experiment, the weight, specific growth rate, feed conversion ratio, and protein efficiency ratio of the fish in the BSD and BGSD diet groups were significantly improved than those of the control group (P < 0.05). Additionally, amylase and trypsin activities were significantly higher (P < 0.05) in both groups compared to the control. Superoxide dismutase and lysozyme activity, which are serum non-specific immune responses, only increased in the BGSD group. The two treatment groups exhibited a marked difference in the intestinal microbiota composition compared to the control group. Furthermore, the treatment groups exhibited an upregulation of IL-6 and NF-κb, coupled with high survival rates when challenged with Edwardsiella tarda. Therefore, dietary supplementation with PM8313 improved the growth performance, digestive enzyme activity, non-specific immunity, and pathogen resistance of red sea bream, in addition to affecting the composition of its intestinal microflora.